BACTERIAL BIOFILMS: THERAPEUTIC CHALLENGES AND TECHNOLOGICAL ADVANCES IN INFECTION CONTROL (CIPEEX, 2025)
Introduction: Bacterial biofilms are complex structures formed by microorganisms adhered to surfaces and embedded in a protective extracellular matrix, representing one of the main mechanisms of antimicrobial resistance in clinical settings. They are estimated to account for up to 80% of persistent hospital infections, posing a major challenge to healthcare systems worldwide. Objective: To analyze the mechanisms of antimicrobial resistance associated with bacterial biofilms and to identify technological innovations applicable to the control of healthcare-associated infections. Methodology: A bibliographic review was conducted between August 2024 and May 2025, using the BVS, SciELO, LILACS, and PubMed databases. Descriptors related to bacterial biofilms, antimicrobial resistance, hospital infections, and innovative technologies were applied, with careful selection of relevant and recent studies. Results and discussion: The studies reviewed indicate that biofilms exhibit multiple resistance mechanisms, including physical barriers, efflux pumps, horizontal gene transfer, and persister cells. Infections associated with medical devices are particularly recalcitrant, showing treatment failure rates up to a thousand times higher than planktonic infections. Emerging technological innovations include metallic nanoparticles, controlled drug delivery systems, antibiofilm peptides, photodynamic therapy, and surface-modified materials. Combined approaches, especially those integrating nanotechnology with conventional antimicrobials, have shown promising results by enhancing biofilm penetration and reducing the required therapeutic doses. Conclusion: Developing innovative strategies for biofilm control represents a critical frontier in clinical microbiology and patient safety. The integration of nanotechnology into conventional protocols offers promising perspectives for addressing biofilm-mediated antimicrobial resistance, highlighting the need for continuous investment in translational research.
Keywords: Bacterial biofilms; Antimicrobial resistance; Hospital infections; Nanotechnology